Analysis of the Genetic Diversity of Endangered Cattle Breeds Based on Studies of Genetic Markers - Madalina Alexandra Davidescu (Agroprint Timisoara, 2021)
In the last 15 years, about 300 breeds out of 6,000 belonging to different species of animals have been identified by the Food and Agriculture Organization of the United Nations (FAO) as extinct. Among the cattle breeds seriously threatened with extinction are the podolian cattle from different parts of Europe. These belong to a group of very old European breeds, having ancestors in Bos primigenius. By studying molecular markers, can be obtained information on the genetic structure of endangered cattle breeds and through identification of some sections of the genome that influence certain traits, can be assess the conservation value of genetic resources of animal origin. The aim of this paper is to identify the main molecular markers used in the analysis of endangered cattle breeds.